Molecular Mechanisms and Epidemiology of Carbapenem-Resistant Escherichia coli Isolated from Chinese Patients During 2002–2017 - Tian, Xuebin (Infect Drug Resist, 2020)
BACKGROUND: The emergence and spread of carbapenem-resistant Escherichia coli (E. coli) pose a serious threat to human health worldwide. This study aimed to investigate the molecular mechanisms underlying carbapenem resistance and their prevalence among E. coli in China. METHODS: A collection of 5796 E. coli clinical isolates were collected from the First Affiliated Hospital of Wenzhou Medical University from 2002 to 2017. Sensitivity to antibiotics was determined using the agar dilution method. The detection of carbapenemases production and the prevalence of resistance-associated genes were investigated through modiﬁed carbapenem inactivation method (mCIM), PCR and sequencing. The mutations in outer membrane porins genes (ompC and ompF) were also analyzed by PCR and sequencing assays. The effect of efflux pump mechanism on carbapenem resistance was also tested. E. coli were typed by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). RESULTS: A total of 58 strains (1.0%) of carbapenem-resistant E. coli were identified. The strains carrying bla(KPC-2) and bla(NDM) accounted for 22.4% (13/58) and 51.7% (30/58), respectively. Among bla(NDM)- positive strains, 27 bla(NDM) genes were assigned to bla(NDM-5), while the remaining three strains were bla(NDM-1), whereas bla(VIM), bla(IMP), bla(OXA-48), and bla(SHV) were not found. The CTX-M-type β-lactamase genes accounted for 96.6% (56/58). In addition, bla(TEM-1) genes were identified in 58.6% of tested strains. In carbapenem-resistant isolates, mutations in OmpC (the majority of mutated sites were D192G and Q104_F141del, accounting for 54.5%) and OmpF (large deletions S75_V127del, W83_D135del and Q88_D135del) were detected. Of note, the antibiotic resistance was not associated with overexpression of efflux pump. Moreover, MLST categorized the 58 carbapenem-resistant isolates into 19 different sequence types. PFGE analysis revealed that homology among the carbapenem-resistant isolates was low and sporadic. CONCLUSION: The bla(NDM) was the principal resistance mechanism of carbapenem-resistant E. coli in the hospital. bla(NDM-5) is becoming a new threat to public health and the alteration of outer membrane porins might help further increase the MIC of carbapenem.